Selected Topics in Applications of Quantum Mechanics - Reza Pahlavani, Mohammad (IntechOpen, 2015)
This book has two sections. The section Selected Topics in Applications of Quantum Mechanics provides seven chapters about different applications of quantum mechanics in science and technology. The section Selected Topics in Foundations of Quantum Mechanics provides seven chapters about the foundations of quantum mechanics. This book is written by a community of expert scientists from different research institutes and universities from all over the world. Without a doubt, quantum mechanics is the greatest discovery of the 20th century. Therefore, its history and foundations are of great interest to scientists and students. This book covers some of the applications of quantum mechanics in nuclear physics, medical science, information technology, atomic physics and material science, as well as selected topics of quantum mechanics through different bases and ideas about quantum mechanics. The basic idea of the publication of this book is to make scientists and researchers, as well as graduate students, familiar with the foundations of quantum mechanics.